RESEARCH OF MODERN EMERGENCY AND RESCUE EQUIPMENT FOR RESCUING PEOPLE FROM UNDER THE COLLAPSES OF BUILDINGS AND STRUCTURES - Prysiazhnyuk, V.; Svirskyi, V. (Municipal economy of cities. Series: «Economy science», 2023)
This publication highlights the relevance of the use of modern emergency rescue equipment with the help of which it is possible to more effectively rescue people from under the rubble of buildings and structures. Examples of some emergency situations during which it was possible to use modern emergency rescue equipment for more effective rescue of people from under the rubble of buildings and structures of various purposes are given. It is noted that the elimination of emergency situations and their consequences is one of the main tasks of civil protection and consists in the implementation of a complex of measures, which include emergency rescue and other urgent works, which are carried out in the event of emergency situations of man-made and natural nature and are aimed at stopping the action of dangerous factors, saving lives and preserving people's health, as well as localization of emergency zones. The term emergency rescue and other urgent works is given - these are works aimed at the search, rescue and protection of the population, the occurrence of destruction and material damage, the localization of the zone of influence of dangerous factors, the elimination of factors that make it impossible to carry out such work or threaten the lives of rescuers. Statistical data on fires in Ukraine for the period 2017-2022 are provided, as well as the annual death toll of people and children using the example of 2022. It is noted about the main types of emergency and rescue equipment used during the liquidation of emergency situations, as well as the training and qualification of units that perform such tasks. The main technical characteristics of several types of mobile devices for effective cutting of various types of building structures are analyzed. Several modifications of mobile devices, possible equipment, structure and principle of operation, as well as the functions they can perform during the liquidation of emergency situations are given It is noted that the Institute of State Administration and Scientific Research on Civil Protection conducted testing and research of modern emergency rescue equipment at the fire-testing ground. Several working points are presented regarding the practical operation of the equipment, as well as the possibilities for cutting various types of building structures. It is also determined that the relevant divisions of the State Emergency Service of Ukraine need to be equipped with such equipment.